Attitudes towards Plagiarism in Business Administration Students from Two Private Universities in Arequipa - Ramos Quispe, Teresa (2019)
The present study seeks to identify, describe and explain attitudes towards plagiarism of Business Administration students from two private universities in Arequipa. A qualitative methodology was used and the analysis content technique was applied. The data were obtained from information from the application of an individual interview guide and a focus group guide. Twenty individual interviews and two focus groups were conducted, totaling 20 newly-admitted students (10 women and 10 men). The categories arising from the answers expressed by the participants were: (a) knowledge of the issue, (b) permissive attitude towards plagiarism, (c) plagiarism as a social facilitator, (d) consequences and (e) preventive attitude. The results show that, for those interviewed, plagiarism is defined as the act of “copying the work of others”, “cheating” or “stealing”. They also concluded that plagiarizing is a common and even institutionalized practice that begins at school and is perfected in the University. Getting good grades is the reason why there are no accusations or discrepancy between students who commit plagiarism and those who do not, since they maintain that plagiarism is not a crime. Finally, the ignorance that you are committing plagiarism, the easy way to do something and fear of failing a course are some of the causes of this cheating action. Among the proposals that the interviewees make to solve this problem is that fact that universities disclose and implement their disciplinary regulations.